2021
DOI: 10.21608/ejhm.2021.171405
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Brachial Index Screening for Peripheral Arterial Disease in Asymptomatic Diabetic Patients

Abstract: Background: Peripheral arterial disease (PAD) is a common macrovascular complication in diabetic patients related to atherosclerosis. Early diagnosis of PAD by ankle brachial index (ABI) is highly critical as this disease results in significant morbidity and mortality. Objectives: To screen for PAD in asymptomatic diabetic patients by using ABI, determining its prevalence and associated risk factors. Patients and Methods: This is a cross-sectional study conducted on 309 diabetic asymptomatic patients in Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…This result was consistent with El-Malky et al, (2021), research on asymptomatic diabetes individuals' ankle brachial index screening for peripheral artery disease, and reported that 36.2% of the studied subjects had peripheral artery disease according to measured ankle brachial index test. (21) This result reflects that the diabetic elderly at risk to foot ulcer need a periodic application of integrating health belief model in a prophylactic diabetic foot care program. Concerning pedal pulse sensation, about one tenth of the studied subjects had UN palpate pedal pulse sensation in the left and right foot pre applying program.…”
Section: Discussionmentioning
confidence: 93%
“…This result was consistent with El-Malky et al, (2021), research on asymptomatic diabetes individuals' ankle brachial index screening for peripheral artery disease, and reported that 36.2% of the studied subjects had peripheral artery disease according to measured ankle brachial index test. (21) This result reflects that the diabetic elderly at risk to foot ulcer need a periodic application of integrating health belief model in a prophylactic diabetic foot care program. Concerning pedal pulse sensation, about one tenth of the studied subjects had UN palpate pedal pulse sensation in the left and right foot pre applying program.…”
Section: Discussionmentioning
confidence: 93%
“…PED is an abnormally reduced arterial disease other than the arteries supplying the heart or brain [1,2]. In the case of narrowing, it is referred to as a coronary artery condition, and cerebrovascular disease is also referred to in the brain [3].…”
Section: Introductionmentioning
confidence: 99%
“…4.6% of persons between the ages of 45 and 50 and 15% of people between 85 and 90 in the developing countries are affected.PAD is equally common in the industrialized world among men and women; however, women are most often affected in the underdeveloped world [23]. In 2015 PAD led to around 52,500 fatalities, up from 16,000 in 1990 [2,24].…”
Section: Introductionmentioning
confidence: 99%